Define f(x)=∑n=0∞x2n+1(2n+1)!f(x)= \sum_{n=0}^{\infty}\frac{x^{2n+1}}{(2n+1)!}f(x)=∑n=0∞(2n+1)!x2n+1 and g(x)=∑n=0∞x2n(2n)!g(x)= \sum_{n=0}^{\infty} \frac{x^{2n}}{(2n)!}g(x)=∑n=0∞(2n)!x2n, where xxx is a real number. Then which of f(x)f(x)f(x) or g(x)g(x)g(x) is greater for all xxx?
Note by A Brilliant Member 7 years, 4 months ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Let us start by writing the Maclaurin Series for ex\displaystyle e^xex, ex=∑n=0∞xnn!\displaystyle e^x = \sum_{n=0}^{\infty} \frac{x^n}{n!}ex=n=0∑∞n!xn e−x=∑n=0∞(−1)nxnn!\displaystyle e^{-x} = \sum_{n=0}^{\infty} (-1)^n \frac{x^n}{n!}e−x=n=0∑∞(−1)nn!xn
Thus, f(x)=ex−e−x2\displaystyle f(x) = \frac{e^x-e^{-x}}{2}f(x)=2ex−e−x, and
g(x)=ex+e−x2\displaystyle g(x) = \frac{e^x+e^{-x}}{2}g(x)=2ex+e−x
It is clear that, g(x)>f(x)g(x)>f(x)g(x)>f(x), as the e−x\displaystyle e^{-x}e−x term is added to the first term in g(x)\displaystyle g(x)g(x), whereas it is subtracted from the first term in f(x)\displaystyle f(x)f(x).
Log in to reply
Good.
f(x)f(x)f(x) is the power series for sinhx\sinh xsinhx and g(x)g(x)g(x) is the power series for coshx.\cosh x.coshx. Use the fact that g(x)−f(x)=coshx−sinhx=e−x>0g(x)-f(x)=\cosh x-\sinh x=e^{-x}>0g(x)−f(x)=coshx−sinhx=e−x>0 for all x.x.x. Therefore, g(x)>f(x)g(x)>f(x)g(x)>f(x) for all x.x.x.
Anish's solution is good as well; I prefer using hyperbolic trig functions for these kind of series though.
Nice.
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Let us start by writing the Maclaurin Series for ex,
ex=n=0∑∞n!xn
e−x=n=0∑∞(−1)nn!xn
Thus,
f(x)=2ex−e−x, and
g(x)=2ex+e−x
It is clear that, g(x)>f(x), as the e−x term is added to the first term in g(x), whereas it is subtracted from the first term in f(x).
Log in to reply
Good.
f(x) is the power series for sinhx and g(x) is the power series for coshx. Use the fact that g(x)−f(x)=coshx−sinhx=e−x>0 for all x. Therefore, g(x)>f(x) for all x.
Anish's solution is good as well; I prefer using hyperbolic trig functions for these kind of series though.
Log in to reply
Nice.